Suivi Thérapeutique Pharmacologique Des Antituberculeux : Quinze Ans d’Expérience - El Bouazzi, Omaima; Belabbes, Soufiane; Moussa, Latifa Ait; Soulaymani-Bencheikh, Rachida; Badrane, Narjis; Bengueddour, Rachid (European Scientific Journal, ESJ, 2016)
Tuberculosis is a world public health problem. Its treatment is based on a set of drugs that can cause many side effects. Liver toxicity remains one of the most common and severe side effect causing treatment failure. The objective of this study is to demonstrate the interest of therapeutic drug monitoring in the treatment of tuberculosis through the experience of the Laboratory of Toxicology and Pharmacology of the Anti Poison Center. This retrospective study involved 1152 patients who had benefited from a determination of plasma levels of first line antitubureculosis drugs (isoniasid, pyrazinamid, rifampicin) during 15 years. 135 patients had developed hepatotoxicity. The study showed that at therapeutic dose, 71.2% of TB patients had plasma concentrations lower than the therapeutic range, and 57.8% of patients had isoniazid plasma concentrations above the therapeutic range. This interindividual variability justifies the need for therapeutic drug monitoring to assess an inadequate response to tuberculosis treatment and prevent the development of hepatotoxicity.